Hubungan Kekuatan Otot Tungkai Terhadap Ketepatan Tendanganpemain Futsal Big Family Deli Serdang - Johanna I B Simbolon; Mustafa Al Haris; Ida Aryani (Jurnal Kesehatan dan Fisioterapi, 2022)
The problem in this study stems from the observation that there are still many futsal players who do not have good kicking skills, it can be seen from their kicks that are not hard and easy to reach by the goalkeeper. Purpose: This study was to determine the relationship between leg muscle strength and kick accuracy on Big Family Deli Serdang futsal players. Research method: this research uses correlational method which aims to see the relationship between variables. The population in this study were all 20 BIG FAMILY futsal players. The sample in this study used a total sampling technique, so the sample amounted to 20 people.  Purpose: this study was to determine the relationship between strength. Data obtained from measurements of the Vertical Jump test to see the strength of the leg muscles, and how much and when to see the accuracy of kicks. The data were analyzed using the Chi-Square test. Based on the results of the research that the authors have described in the previous chapter, the asimp.Sig value is 0.730 > 0.05, it can be concluded that there is no significant relationship between leg muscle strength and ball kick accuracy in Big Family Deli Serdang futsal players. Keywords: Limb Muscle Strength, Kicking Accuracy